Organoleptic and Hedonic Quality of Salted Chicken Eggs with the Brick Salting Method: Desa badas kec sumobito kab jombang - Imm Juwari (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This study aims to analyze the organoleptic and hedonic quality of salted chicken eggs against the duration of incubation using the brick salting method. This study has 4 variants of incubation time with the code: ABB with a storage time of 3 days, BCC with a storage time of 5 days, CDD, with a storage time of 10 days and DFF with a storage time of 15 days. The method used in this study is data collection through organoleptic tests and hedonic tests with panelists. The results showed that the longer the storage, there was an increase in salt content and significant changes in the texture and taste of salted eggs. This study is an experimental RAL study involving 10 panelists. Sensory analysis used advanced ANOVA and BNT tests with a level of 5%. The results showed that the DFF egg variant had the softest texture among all salting treatments. Keywords: Salted eggs, storage, quality, organoleptic, physicochemical.